RANCANG BANGUN SISTEM INFORMASI POINT OF SALE BERBASIS WEB - Yanti, Chagu Hospita; Arnomo, Sasa Ani (Computer Science and Industrial Engineering, 2023)
The development of the business world encourages companies to always try to improve the quality of products and services to consumers. Goods purchase services can be done electronically and can also be done online. The implementation of these business solutions is a commitment to increasing customer competitive advantage in terms of efficiency, effectiveness, performance, and business development. This study aims to design and develop a point of sale (POS) application to support a purchasing service system that can help CV Berdikari owners in data management. Making this POS application begins with collecting all the data needed using observation, interview, and literature study methods, designing Model Prototyping applications with application design tools in the form of flowcharts and Unified Modeling Language (UML) until the implementation of this POS application. With the implementation of this point of sales (POS) application, it can help users who are directly related to this POS application, especially customers, employees and owners in the process of managing reports and controlling their business activities.